Differences in Ocular Complications Between Candida albicans and Non-albicans Candida Infection Analyzed by Epidemiology and a Mouse Ocular Candidiasis Model - Abe, Masahiro; Kinjo, Yuki; Ueno, Keigo; Takatsuka, Shogo; Nakamura, Shigeki; Ogura, Sho; Kimura, Muneyoshi; Araoka, Hideki; Sadamoto, Sota; Shinozaki, Minoru; Shibuya, Kazutoshi; Yoneyama, Akiko; et al. (Frontiers in Microbiology, 2018)
Objectives:Candida species are a major cause of hospital infections, including ocular candidiasis, but few studies have examined the propensities of specific species to invade the eye or the unique immunological responses induced. This study examined the frequency and characteristics of species-specific Candida eye infections by epidemiology and experiments using a mouse ocular candidiasis model. Methods: We reviewed medical records of candidemia patients from January 2012 to March 2017. We also evaluated ocular fungal burden, inflammatory cytokine and chemokine profiles, and inflammatory cell profiles in mice infected with Candida albicans, Candida glabrata, or Candida parapsilosis. Results: During the study period, 20 ocular candidiasis cases were diagnosed among 99 candidemia patients examined by ophthalmologists. Although C. parapsilosis was the most frequent candidemia pathogen, only C. albicans infection was significantly associated with ocular candidiasis by multivariate analysis. In mice, ocular fungal burden and inflammatory mediators were significantly higher during C. albicans infection, and histopathological analysis revealed invading C. albicans surrounded by inflammatory cells. Ocular neutrophil and inflammatory monocyte numbers were significantly greater during C. albicans infection. Conclusion:Candida albicans is strongly associated with ocular candidiasis due to greater capacity for invasion, induction of inflammatory mediators, and recruitment of neutrophils and inflammatory monocytes.